Enantioselective Cycloaddition Reactions of Ketenes Catalyzed by N-Heterocyclic Carbenes - Chen, Xiang-Yu; Ye, Song (Synlett, 2013)
This account summarizes recent research in our group on the development of N-heterocyclic carbene (NHC) catalyzed cycloaddition reactions of ketenes. The NHCs were found to be efficient catalysts for the enantioselective [2+2]-, [2+2+2]-, [3+2]-, and [4+2]-cycloaddition reactions of ketenes with various electrophiles, such as imines, carbonyl compounds, oxaziridines, oxodienes and azadienes. The NHC-catalyzed [4+2] cycloaddition of α,β-unsaturated acyl chlorides was also investigated.1 Introduction2 [2+2] Cycloaddition of Ketenes 2.1 With Carbon–Nitrogen Double Bonds2.2 With Carbon–Oxygen Double Bonds2.3 With Oxygen–Nitrogen and Nitrogen–Nitrogen Double Bonds2.4 With X=Y=Z Bonds3 [3+2] Cycloaddition of Ketenes 4 [4+2] Cycloaddition of Ketenes5 [4+2] Annulation of Unsaturated Acyl Chlorides6 Conclusions and Outlook
Keywords: ketenes; N-heterocyclic carbene; cycloadditions; enantioselectivity; α,β-unsaturated acyl chlorides